Physics Stack Exchange is a question and answer site for active researchers, academics and students of physics. Join them; it only takes a minute:

Sign up
Here's how it works:
  1. Anybody can ask a question
  2. Anybody can answer
  3. The best answers are voted up and rise to the top

I have been given the Lorentz generator $$J_{ab}=\lambda_a \frac{\partial}{\partial \lambda^b}+a\leftrightarrow b$$

I know $\frac{\partial}{\partial \lambda^b}\lambda_a=\epsilon_{ba}$ and $A_a=A^b\epsilon_{ab}$ (? not sure about these two). I want to show that this acting on a spinor bracket gives zero as this is supposed to be Lorentz invariant. Say I have a bracket $\langle A B \rangle = A_a B_b \epsilon^{ab}$ and now I act with $J_{ab}$ on it w.r.t $A$, i.e.

$$\begin{split}J^A_{ab}\langle A B \rangle &=(A_a \frac{\partial}{\partial A_b}+a\leftrightarrow b) A_cB_d\epsilon^{cd}\\&=A_a\epsilon_{bc}B_d\epsilon^{cd} + A_b\epsilon_{ac}B_d\epsilon^{cd}\\&=A_a\epsilon_{bc}B_{c}+A_b\epsilon_{ac}B_c\\&=?\end{split}$$

Where do I go wrong? Could someone please help me out? Why doesnt it sum to zero?

share|cite|improve this question
up vote 4 down vote accepted

Firstly, I don't think your convention for the derivative is consistent with how you lower the index on $\lambda^b$. Let us start with $$ \frac{\partial}{\partial \lambda^b} \lambda^a = \delta_b^a $$ If you lower the index on $\lambda^b$ you get $$ \lambda_a = \epsilon_{ac} \lambda^c $$ Putting this together gives $$ \frac{\partial}{\partial \lambda^b} \lambda_a = \epsilon_{ac} \frac{\partial}{\partial \lambda^b} \lambda^c = \epsilon_{ab} = -\epsilon_{ba} $$ which has a different sign from what you have.

Furthermore, the spinor bracket you write is Lorentz invariant if you transform both spinors at the same time. The actions of $J^A$ and $J^B$ on $\langle AB \rangle = \epsilon_{cd} A^c B^d$ is given by \begin{align} J_{ab}^A\, \epsilon_{cd} A^c B^d &= \left(A_a \frac{\partial}{\partial A^b} + A_b \frac{\partial}{\partial A^a} \right) \, \epsilon_{cd} A^c B^d \\ &= \epsilon_{cd} \left( A_a \delta_b^c + A_b \delta_a^c \right) B^d = +(A_a B_b + B_b A_a) \\ % J_{ab}^B\, \epsilon_{cd} A^c B^d &= \left(B_a \frac{\partial}{\partial B^b} + B_b \frac{\partial}{\partial B^a} \right) \, \epsilon_{cd} A^c B^d \\ &= \epsilon_{cd} A^c \left( B_a \delta_b^d + B_b \delta_a^d \right) = -(A_a B_b + B_b A_a) \end{align} so if you sum them the transformation of $A$ is cancelled by the transformation of $B$.

share|cite|improve this answer
Thanks! Now i get it :) – Sanji Jun 7 '13 at 9:51

Your Answer


By posting your answer, you agree to the privacy policy and terms of service.

Not the answer you're looking for? Browse other questions tagged or ask your own question.